2022
DOI: 10.1007/s12520-022-01656-6
|View full text |Cite
|
Sign up to set email alerts
|

Multi-analytical study of the medieval wall paintings from the rupestrian church Grotta del Crocifisso at Lentini (eastern Sicily): new evidence of the use of woad (Isatis tinctoria)

Abstract: This study presents the results of the examination and characterisation of the wall paintings that decorate the rupestrian church named Grotta del Crocifisso, which is located in the territory of Lentini (eastern Sicily, few tens of kilometres from Catania and Syracuse). The earliest mural paintings in the church date back to the twelfth century AD. A multi-analytical approach was adopted for the characterisation of stone materials, secondary degradation products, and pigments. For this purpose, the following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The frescoes in this church, which date back to the 9th to tenth century, present a direct derivation from the Byzantine stylistic features [ 26 ]. In the rupestrian church Grotta del Crocifisso (Lentini, Italy), the earliest mural paintings date back to the twelfth century, and these wall paintings constitute the greatest wealth of this church [ 27 ]. Located in Castellammare del Golfo ( Trapani, Italy), Santa Margherita ’s cave is a natural cave, containing the remains of paintings, which can date back to thetwelfth century.…”
Section: Major Distribution Areas Of Muralsmentioning
confidence: 99%
See 1 more Smart Citation
“…The frescoes in this church, which date back to the 9th to tenth century, present a direct derivation from the Byzantine stylistic features [ 26 ]. In the rupestrian church Grotta del Crocifisso (Lentini, Italy), the earliest mural paintings date back to the twelfth century, and these wall paintings constitute the greatest wealth of this church [ 27 ]. Located in Castellammare del Golfo ( Trapani, Italy), Santa Margherita ’s cave is a natural cave, containing the remains of paintings, which can date back to thetwelfth century.…”
Section: Major Distribution Areas Of Muralsmentioning
confidence: 99%
“…Using this method, the composition of the pigments in the fifteenth century Thubchen Lakhang monastery was presented, and it was found that the blue pigments were azurite (C 2 H 2 Cu 3 O 8 ) and sometimes with lazurite ((Na, Ca) 8 [(S, Cl, SO 4 , OH) 2 |(Al 6 Si 6 O 24 )]), the red and orange paint layers were orpiment (As 2 S 3 ) and vermilion (HgS), the brown and green color decorations are composed by red ochre (Fe 2 SO 3 ) and malachite (Cu 2 CO 3 (OH) 2 ) [ 89 , 90 ]. For the murals in the rupestrian church Grotta del Crocifisso at Lentini in Italy, X-ray fluorescence and scanning electron microscopy can easily identify the red, yellow, brown, and green pigments [ 27 ]. Using multiple techniques including binocular microscopy, field emission scanning electron microscopy, X-ray spectroscopy, X-ray fluorescence, Fourier transform infrared spectroscopy, thin-film X-ray diffraction, micro-Raman spectroscopy, and Gas chromatography-mass spectrometry, the materials composition in the sixteenth century Orthodox Syrian Church in south India were determined.…”
Section: Materials Composition and Research Techniquesmentioning
confidence: 99%